2007
DOI: 10.1111/j.1365-2834.2007.00759.x
|View full text |Cite
|
Sign up to set email alerts
|

Recognition and management of critical illness by midwives: implications for service provision

Abstract: This study has yielded important insights into midwives' management of critical illness. Possible mechanisms to enhance the quality of service provision, and midwife support in this area are highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 36 publications
0
9
1
1
Order By: Relevance
“…Training covered umbilical cord prolapsed, 42 vaginal breech delivery, 21 pre-eclampsia, 31,43 PPH, 15,28,44 shoulder dystocia, 20,24,27,30,45 and combinations of the above. 5,25,26,[32][33][34]37,42,46 Notably, there were no studies of non-technical skills (leadership, teamwork, situation awareness, decision making) in undergraduate midwifery but a number that examined teamwork skills in a multi-professional setting. 29,[31][32][33][34]36,44,47,48 Pedagogical approach Reported pedagogical approaches also varied, ranging from low to high fidelity (Table 1).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Training covered umbilical cord prolapsed, 42 vaginal breech delivery, 21 pre-eclampsia, 31,43 PPH, 15,28,44 shoulder dystocia, 20,24,27,30,45 and combinations of the above. 5,25,26,[32][33][34]37,42,46 Notably, there were no studies of non-technical skills (leadership, teamwork, situation awareness, decision making) in undergraduate midwifery but a number that examined teamwork skills in a multi-professional setting. 29,[31][32][33][34]36,44,47,48 Pedagogical approach Reported pedagogical approaches also varied, ranging from low to high fidelity (Table 1).…”
Section: Introductionmentioning
confidence: 92%
“…29,[31][32][33][34]36,44,47,48 Pedagogical approach Reported pedagogical approaches also varied, ranging from low to high fidelity (Table 1). Verbal and paper and pencil approaches were described, 5,39 virtual electronic based scenarios, 15,38,49 and manikin based studies. 10,13,14,16,18,20,22,23,31,32,34,37,41,44,45 Standardised patients, for example a female playing the part of a woman during birth, were reported 7,17,43 and combination approaches (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the increased numbers using our unit, it would be wrong to think it had been easy to set up and run. Qualitative studies have highlighted the difficulties faced by midwives in caring for the critically ill mothers [18] and Dr Crawford also alluded to this in expressing the unease of working in an HDU environment. In latter years, we have found that the input from our Lead Figure 3 Histogram depicting the duration of stay in the high dependency unit during the audit period July 03-June 07.…”
Section: Discussionmentioning
confidence: 99%
“…The interviews, which were digita lly recorded, were conducted in an area free from distraction. At the close of each interview, the researcher provided a summary of the coach's response to verify understanding and accuracy (Bench, 2007). This summary afforded the main researcher the opportunity to highlight the most salient points raised by the coach at each pertinent point in the interview and to ensure congruence between the researcher's interpretatio n and the coach's intention.…”
Section: Insert Figure 1 Herementioning
confidence: 99%